Peningkatan Skill Komunikasi Guru Sebagai Pengembangan Model Pembelajaran Dalam Keefektifan Proses Belajar Siswa (International Forum of Researchers and Lecturers, 2023)
When communicating, a person always has a message in the communication he conveys just like a teacher who has a message to students. Through this communication one can express ideas, opinions and emotions to other participants. Teaching materials that act as messages in teacher communication and teachers who act as communicants and then student participants who act as participants in the learning process. If there is no communication, there will be no logging process educators. The communication skills of a teacher will affect how well they master the learning model applied in their learning. The learning model consists of various types and through learning communication it will reach well to students and the learning that occurs can run effectively. The chosen learning model and teacher communication skills are a way to build a very important learning process for effective learning to be realized. The ability of a teacher to communicate is a teacher's competence listed in the Law in order to achieve effective learning. In this article the method used is a type of qualitative research that studies and or collects data in the form of sentences that are separated by categories to obtain conclusions. The conclusion that can be obtained is that communication skills are very influential with the learning model carried out and the effectiveness of the learning process.